1998
DOI: 10.1113/expphysiol.1998.sp004087
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on kinetics of oxygen uptake and phosphocreatine in humans during exercise

Abstract: SUMMARYWe compared the kinetics of oxygen uptake (VO2) and phosphocreatine (PCr) during the adjustment to and recovery from plantar flexion exercise in moderately active older (n = 10, 66.9 years) and younger (n = 10, 27-5 years) individuals. VO2 kinetics were similar in the two groups, with time constants (T)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 27 publications
(57 reference statements)
4
39
0
1
Order By: Relevance
“…This result is consistent with previous studies of muscle bioenergetics in aging (7,43,48,49). The current study also extends information regarding submaximal contraction intensities (7,43), where we found a greater oxidative ratio in both older groups compared with young at 50% MVC, but not at 20% MVC. This greater relative ATP OX in the older groups is also consistent with our observed main effect of group for the absolute ATP OX (Fig.…”
Section: Atp Productionsupporting
confidence: 82%
“…This result is consistent with previous studies of muscle bioenergetics in aging (7,43,48,49). The current study also extends information regarding submaximal contraction intensities (7,43), where we found a greater oxidative ratio in both older groups compared with young at 50% MVC, but not at 20% MVC. This greater relative ATP OX in the older groups is also consistent with our observed main effect of group for the absolute ATP OX (Fig.…”
Section: Atp Productionsupporting
confidence: 82%
“…With regard to in vivo oxidative capacity of the MG, the present results are consistent with two prior studies (Chilibeck et al 1998;Wray et al 2009). They are not consistent with the results of one in vivo study (McCully et al 1991) and two in vitro (enzyme activities) studies (Coggan et al 1992;Houmard et al 1998), all of which showed lower oxidative capacity in the O subjects.…”
Section: Age and Oxidative Capacitysupporting
confidence: 82%
“…The TA is largely composed of type I fibers (75 % type I; Gregory et al 2001), while the MG is mixed in fibertype composition (50 % type I; Edgerton et al 1975). Furthermore, while most studies of the TA do not report lower oxidative capacity in O adults (Kent-Braun and Ng 2000; Lanza et al 2005Lanza et al , 2007Larsen et al 2012b;Tevald et al 2010), reports on the MG differ, with studies reporting either lower (McCully et al 1991;Coggan et al 1992;Houmard et al 1998) or similar (Chilibeck et al 1998;Wray et al 2009) oxidative capacity in O compared to Y adults. Based on the previously discussed evidence that age-related changes in several aspects of muscle performance are smaller in the TA than the MG, we hypothesized that oxidative capacity would be preserved in the TA, but not the MG, of O subjects.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Skeletal muscle energetics were assessed through 31 P NMR spectroscopy (Fig. 1B), and from this spectra PCr depletion and recovery kinetics were evaluated as an index of muscle oxidative demand and capacity, respectively (6,14,24). Both of these measurements are unique in that they allow for the probing of perfusion and metabolism in a noninvasive manner with very high-spatial and temporal resolution and do so in a focused ROI within the exercising muscle tissue.…”
Section: Discussionmentioning
confidence: 99%